Lipoprotein apheresis – Shortening of treatment intervals reduces cardiovascular events: Case reports. (December 2019) - Berent, Theresa; Berent, Robert; Sinzinger, Helmut
Abstract: Background: Lipoprotein (Lp-) apheresis is a life-long therapy, usually performed in weekly intervals. In some cases, however, atherosclerotic disease progresses despite adequate therapy with weekly Lp-apheresis and maximal lipid lowering medication. In an attempt to improve the effectiveness of therapy, we temporarily shortened treatment intervals of Lp-apheresis in patients with elevated lipoprotein(a) (Lp(a)) and further progression of coronary atherosclerosis despite weekly Lp-apheresis and maximal lipid lowering medication. Methods: We illustrate three case reports of patients with elevated Lp(a), who underwent regular weekly Lp-apheresis treatment for secondary prevention. The intensified treatment protocol contained three therapies in two weeks (alternating 2 per week and 1 per week). Results: The shortening of treatment intervals achieved a stabilization of atherosclerotic disease in case 1. After a total of 68 therapies in 52 weeks (1.31 sessions/week) the elective coronary angiography revealed excellent long-term results. In case 2, the intensified treatment protocol is still ongoing. The patient reported a decrease in angina pectoris and an increase in exercise capacity since the beginning of more frequent therapy sessions. In some cases, as it is shown in case 3, a fast decision for shortening the treatment intervals is necessary. Conclusions: The intensified treatment regimen resulted in an improvement in clinical symptoms and no further progression of atherosclerosis. In conclusion, shorter therapeutic Lp-apheresis intervals, at least temporarily, should be considered in patients who suffer from clinical and/or angiographic progression of atherosclerosis, despite maximal lipid lowering medication and weekly Lp-apheresis.